Can a Search Engine … [Be Held Liable for Defamation]? - Ashby, Caitlin (Victoria University of Wellington Law Review, 2025)
When defamation occurs online, it has become increasingly common for complainants to seek compensation from the internet intermediaries (such as internet service providers, search engine providers and website hosts) which conceivably bear some responsibility for those publications. The liability of search engine providers is particularly contentious. This is because the defamatory words which appear in autocomplete suggestions and snippets are unique publications made by the search engine, but without the direct knowledge or approval of any human actor. The only case in New Zealand to have addressed this issue, A v Google, suggests that search engines might be liable as publishers, but is ultimately inconclusive. This article seeks to clarify the extent to which providers of search engines should be held liable in New Zealand for the defamatory content they disseminate by comparing the liability doctrines which have been applied overseas and assessing the policy implications of each approach. Ultimately, the author concludes that it would be disingenuous to preclude liability on the basis that a search engine is a mere facilitator of the defamatory content it disseminates. Instead, this article argues that liability should arise only once the search engine provider has actual knowledge of the defamatory words and has failed to remove them within a reasonable time, so as to support an inference that the search engine provider has assumed some responsibility for the publication. The assumption of liability doctrine is preferred as it provides an avenue for victims to seek compensation from those at fault, without encroaching on freedom of expression beyond what is demonstrably justified.